Coach's effectiveness mediate longitudinal effects of transformational leadership behavior on athlete outcomes. / Ahmad Fikri Mohd Kassim - Mohd Kassim, Ahmad Fikri (Universiti Teknologi MARA, 2021)
The present study aimed to investigate whether athlete perceptions of coaching effectiveness mediate the longitudinal relationships between perceptions of transformational leadership (TL) and athlete outcomes. 174 team-sport athletes (Rugby = 35, Basketball = 46, Football = 93) participated by completing psychometric measures of the study variables at two time points (retention rate = 93.5%). Data analyses revealed athletes' perceptions of their coach's character-building effectiveness at Time 1 did not mediate a negative predictive effect of perceptions of coach appropriate role model behaviour at Time 1 on athlete antisocial opponent behaviour at Time 2. However, such perceptions did mediate a negative effect of perceptions of coach appropriate role model behaviour at Time 1 on athlete antisocial teammate behaviour at Time 2. Further, athletes' perceptions of their coach's motivation effectiveness at Time 1 mediated a positive effect of coach individual consideration behaviour at Time 1 on trust at Time 2. The findings of this study suggest athletes' perceptions of their coach's transformational leadership behaviour may at times influence athlete outcomes through changes in athletes' perceptions of their coach's effectiveness.